Introducing the Walking Threads Project - Loovers, Jan Peter Laurens; Esposito, Paola (The Unfamiliar, 2015)
The following collections of essays and creative interventions of Paola Esposito, Ragnhild Freng Dale, Jan Peter Laurens Loovers, and Brian Schultis are the result of individual attempts to recall, reflect, and make sense of an exercise called "Walking threads". It also expressed a commitment to allow experiences to grow within and between the authors in an exercise of attunement.